Religion, Statelessness, and Belonging: A Jewish Perspective - Weissman, Debbie (The ecumenical review, 2019)
Before 1948, and stretching back more than 1800 years, the Jewish people suffered all the problems of statelessness. The Zionist movement, 1897-1948, strove to end the condition of Jewish exile and statelessness. The great historical irony and tragedy is that the establishment of the State of Israel brought about the Nakba, the catastrophe, of the Palestinian people. Both the Israelis and the Palestinians see themselves as the victims of the conflict. They seem to be competitors in what I call a "suffering sweepstakes." One of the problems with victimhood is that it prevents victims from assuming responsibility for their actions, including the victimization of others. In the Israeli-Palestinian conflict, both sides are victims and both sides are victimizers. The least helpful thing people can do - and regrettably many well-meaning people do this - is to portray the situation in terms of a zero-sum game, in which, if you're pro-Palestinian, you must be anti-Israeli, and vice versa. We must be both pro-Palestinian and pro-Israeli, because we are pro-people and, therefore, pro-peace. The achievement of peace necessitates a two-state solution based on some recognition of the two narratives. The best fulfilment of Zionism will come when there is a Palestinian state alongside the State of Israel.